A versatile valving toolkit for automating fluidic operations in paper microfluidic devices. Issue 6 (21st January 2015) - Toley, Bhushan J.; Wang, Jessica A.; Gupta, Mayuri; Buser, Joshua R.; Lafleur, Lisa K.; Lutz, Barry R.; Fu, Elain; Yager, Paul
Abstract : A versatile, powerless, valving and automation toolkit for paper microfluidic devices that uses absorbent expanding elements as actuators is presented. Abstract : Failure to utilize valving and automation techniques has restricted the complexity of fluidic operations that can be performed in paper microfluidic devices. We developed a toolkit of paper microfluidic valves and methods for automatic valve actuation using movable paper strips and fluid-triggered expanding elements. To the best of our knowledge, this is the first functional demonstration of this valving strategy in paper microfluidics. After introduction of fluids on devices, valves can actuate automatically after a) a certain period of time, or b) the passage of a certain volume of fluid. Timing of valve actuation can be tuned with greater than 8.5% accuracy by changing lengths of timing wicks, and we present timed on-valves, off-valves, and diversion (channel-switching) valves. The actuators require ~30 μl fluid to actuate and the time required to switch from one state to another ranges from ~5 s for short to ~50 s for longer wicks. For volume-metered actuation, the size of a metering pad can be adjusted to tune actuation volume, and we present two methods – both methods can achieve greater than 9% accuracy. Finally, we demonstrate the use of these valves in a device that conducts a multi-step assay for the detection of the malaria protein P f HRP2. Although slightly more complex than devices that do not have moving parts, this valving and automation toolkit considerably expands the capabilities of paper microfluidic devices. Components of this toolkit can be used to conduct arbitrarily complex, multi-step fluidic operations on paper-based devices, as demonstrated in the malaria assay device.